Методика експериментального дослідження в’язкопружних властивостей ортотропного матеріалу - Мартиненко, Володимир Геннадійович (НТУ "ХПІ", 2015)
Представлено методику для проведення експериментального дослідження в’язкопружних властивостей ортотропного матеріалу. Розв’язана задача розтягнення та зсуву постійними навантаженнями тонкої в’язкопружної ортотропної пластинки. Розроблено спосіб апроксимації експериментальних даних, отриманих у різні моменти часу та для різних температурних точок, з метою визначення пружних властивостей та ядра релаксації ортотропного матеріалу, якому характерна в’язкопружність, ступінь анізотропії якої визначається ступенем анізотропії пружних властивостей, за допомогою методу найменших квадратів.

The paper considers the techniques for the conducting of an experimental investigation of viscoelastic properties of an orthotropic material. The solved problem of stretching and shearing of a thin viscoelastic plate by constant loads enabled an analytical determination of relaxation kernels. The developed method of a fitting of experimental data gained at different time and temperature points allowed a determination of elastic properties and a relaxation kernel of an orthotropic material with viscoelastic properties, whose the degree of anisotropy is determined by the degree of anisotropy of the elastic properties, using the method of least squares. The described methodology will be used for the estimation of the mechanical properties of thin composite structures.
Methodology of experimental investigation of viscoelastic properties of orthotropic material
Keywords: ядро релаксації; метод найменших квадратів; температура; композитний матеріал; relaxation kernel; method of least squares